On Identity - Sidorek, Sidorek (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2019)
The structure of identity forms the main point of discussion in this essay. The initial question ’Who am I?’ is divided into fragmentary questions: ’Who have I become?’ and ’Who am I going to be?’, which are later contrasted with similar questions: ’Who are we?’and ’Who are we all?’. The analysis of relations between these questions and their sensible answers, reveals a prescriptive factor which is explained by appealing to some particular understanding of the word ’good’, manifesting in such feelings as pride, shame and sense of guilt. It leads to a fragmentary definition: our identity consists of everything we are proud or ashamed of. There are some limitations of our freedom in the ruling of identity in that meaning, however, and they are described further in this essay.(original abstract)